Factors predicting singers’ work efficiency and singers’ singing peak - Huang, Xuejie; Ang, Mei Foong (Sciendo, 2024)
The research focusses on understanding the controls and predicting singers’ work efficiency, which is measured by rework times (RwT) in the recording studios. We conducted a comprehensive literature synthesis to identify a set of nine critical factors combining advancements in both acoustic field and recording practice. We measured each of these potential variables while 10 individual singers performed the same original song independently. The pieces of music sentences (n = 380) were analyzed by the multiple linear regression method. We found that: 1. In the recording process, the RwT of a singer are predicted mainly by intensity, singing duration (SinD) and rhythm consistency. 2. SinD mediates the connection between intensity and RwT. 3. A singing peak exists in the performance.